The limit of sulphide adaptation in the sulphide-sensitive cyanobacterium "Microcystis aeruginosa" - Martín-Clemente, Elena; Melero-Jiménez, Ignacio José; Bañares-España, Elena; Flores-Moya, Antonio; García-Sánchez, María Jesús (Universidad de Málaga/Sociedad Española de Microbiología, 2019)
Although sulphide has played an important role in the evolution of photosynthesis, it produces a lethal effect on most photosynthetic organisms due to its redox activity on certain enzymes, inhibiting oxygenic photosynthetic and respiratory electron transport. However, cyanobacteria vary in sulphide tolerance, showing different degrees of sulphide resistant oxygenic photosynthesis and even some taxa have the capacity to perform anoxygenic sulphide-dependent photosynthesis. Microcystis aeruginosa is a sulphide-sensitive species. However, it is known that genetic adaptation of aquatic photosynthetic microorganisms to selective agents can be rapidly achieved, even at lethal levels, as the consequence of single mutations. The aim of this work was to determine the maximum sulphide concentration to which this sulphide-sensitive species is able to adapt in order to shed light on the process of sulphide adaptation in cyanobacteria. We used three M. aeruginosa strains, Ma1Vc, Ma5Vc and MaAVc, isolated from a non-sulphureous environment, and whose lethal doses were 0.10, 0.16 and 0.20 mM sulphide, respectively. To study the adaptation of these strains to sulphide a modified ratchet experiment was carried out [...]. The M. aeruginosa strains reached different limits of sulphide adaptation. Ma5Vc and Ma1Vc strains adapted up to 0.40 mM sulphide, i.e. 2,5-fold and 4-fold their initial lethal doses, respectively. However, the MaAVc strain, which showed an initial higher sulphide tolerance, adapted up to only 0.27 mM. Sulphide-lethal dose and photosynthetic performance of the resistant strains obtained in the ratchet experiment were characterized. The lethal dose of the M. aeruginosa Ma1Vc and Ma5Vc mutant strains was 0.40 and 0.72 mM sulphide, respectively. These resistant strains showed lower growth and photosynthetic rates than wild-type ones in the absence of sulphide, which indicates the physiological cost of the mutation conferring sulphide resistance.
Libro de resúmenes de ponencias y comunicaciones. XXVII Congreso Nacional de Microbiología 2019, p 276 , ISBN 978-84-09-02644-9
Keywords: Cianobacterias; Sulfuros; Microbiología -- Congresos; Cyanobacteria; Adaptation; Sulphide